Analisis Sistem Pengendalian Intern Pemerintah Dalam Pengelolaan Bantuan Operasional Sekolah - Purwita Sari; Feby Yoana Siregar (ITB AAS INDONESIA Surakarta, 2021)
This study aims to analyze the implementation of the government's internal control system in the management of school operational assistance at SDN 060864. The research method is a descriptive type of research with a qualitative approach, namely solving the problem under investigation by describing the state of the institution that is running the government internal control system based on the facts. through interviews and direct observations in the field. The results of this study indicate that SDN 060864 has implemented the five elements of government internal control which include the control environment, risk assessment, control activities, information and communication, and monitoring so that the financial management of school operational assistance funds (BOS) in SDN 060864 can be accounted for in a transparent and transparent manner. accountability in accordance with the principles of financial management according to Law Number 20 of 2003.